Compressive behavior of Body-Centered-Cubic (BCC)-like ultra-lightweight Carbon Fiber Reinforced Polymer (CFRP) lattice-based sandwich structures - Vitale, Pablo (2024)
3D lattice structures comprise a connected network of segments that allow positioning of the base material where needed while maintaining an open-cell characteristic. These structures represent an ideal lightweight core material for high-performance sandwich panels. This work presents, for the first time, the performance of latticebased cores fabricated via indirect additive manufacturing using pultruded Carbon Fiber Reinforced Polymer (CFRP) rods. The CFRP sandwich panels were tested under out-of-plane compression, and their compressive properties and failure modes were predicted via analytical and FE analyses, later contrasted with mechanical testing. Finally, the study compares favorably with similar core materials found in the literature.